A Deadly Spontaneus Hemopneumothorax: A Case Report - Muhammad Zulfikar Karim Chan; Kelly Christy; Herman Darmawan; Brilliant Bergant (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Spontaneous hemopneumothorax (SHP) is a subtype of hemopneumothorax in which there is an accumulation of blood and air in the pleural space without trauma or other definitive cause. Spontaneous hemopneumothorax is a rare disease. Case presentation: A man, aged 32 years, came with a complaint of sudden shortness of breath due to a right hemopneumothorax patient who was put on a chest tube insertion. It looked like 1500 cc of blood came out accompanied by an air component. Next, the chest tube is connected to the water-sealed drainage. The patient found a decrease in Hb from 15 mg/dl to 12 mg/dl. In the next nine hours, the patient's Hb became 10 mg/dl. As a result of this condition, the patient underwent an emergency thoracotomy to evaluate the source of bleeding, where the patient's source bleeding was found to be an arterial vein malformation (AVM) at the apex of the lung attached to the chest wall. Anatomical and pathological examination showed confirmed arterial vein malformation. Conclusion: Spontaneous hemopneumothorax, in this case, is a rare case caused by arterial-vein malformation. The right decision in patient management will determine the outcome and outcome of the treatment given.